2009
DOI: 10.1103/physrevc.79.044002
|View full text |Cite
|
Sign up to set email alerts
|

Production of the ω meson in thepdHe3ωreaction at 1450 MeV and 1360 MeV

Abstract: The production of ω mesons in the pd → 3 He ω reaction has been studied at two energies near the kinematic threshold, Tp = 1450 MeV and Tp = 1360 MeV. The differential cross section was measured as a function of the ω cm angle at both energies over the whole angular range. Whereas the results at 1360 MeV are consistent with isotropy, strong rises are observed near both the forward and backward directions at 1450 MeV. Calculations made using a two-step model with an intermediate pion fail to reproduce the shape… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The authors found the one-and two-body mechanisms to contribute 2-3 orders of magnitude lesser than the three-body mechanism and produced backward peaked angular distributions (consistent with the findings of [58]). Similar problems in reproducing the angular distributions for the p d → 3 He ω reaction also have been reported in Refs [118,119]. A comparison of the one and two step processes in the 12 C(p, η) 13 N reaction can be found in [120].…”
Section: One Two and Three Body Mechanismssupporting
confidence: 74%
“…The authors found the one-and two-body mechanisms to contribute 2-3 orders of magnitude lesser than the three-body mechanism and produced backward peaked angular distributions (consistent with the findings of [58]). Similar problems in reproducing the angular distributions for the p d → 3 He ω reaction also have been reported in Refs [118,119]. A comparison of the one and two step processes in the 12 C(p, η) 13 N reaction can be found in [120].…”
Section: One Two and Three Body Mechanismssupporting
confidence: 74%
“…To state a few examples, these resonances play an important role in understanding N − N interaction [1, 2], in describing cross sections for the reaction with meson-nucleus final states (for instance, see Refs. [3][4][5][6]), in approaching some fundamental issues, like, existence of multiquark states [7], occurrence of OZI violating processes [8], etc. Such relevance serves as a motivation for the dedicated efforts made by several groups in extracting information related to N * and ∆ resonances through different approaches: like, partial wave analysis of the relevant data [9], within quark models [10], unitarized dynamical models (see, for example, Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The normalisation was achieved by comparing data on backward going η mesons from pd → 3 Heη from SPES IV [11] and SPES III [12] with the corresponding data from this work using the method described in Refs. [23] and [25]. The normalisation uncertainty of the measured cross sections and is 29% at 1360 MeV and 12% at 1450 MeV.…”
Section: The η Angular Distributionmentioning
confidence: 99%